SOSIALISASI BAHAYA YANG TERSEMBUNYI DIBALIK JUDI ONLINE BAGI MAHASISWA - Nopriansyah, Waldi; Noviani, Dwi; Maleha, Nova Yanti; Choiriyah, Choiriyah (LPPM Universitas Bina Bangsa, 2024)
Online gambling can now be played by every element from children and adults to the elderly. Online gambling has dangerous impacts such as financial losses, stress, crime, and even death. Based on this, it is necessary to socialize with students at the Universitas Indo Global Mandiri Palembang campus to discover the dangers behind online gambling. The method used in this socialization activity is identifying problems, planning, and involving government agencies. In its implementation, this socialization method is also carried out using lectures, case studies, and discussions to evaluate participant understanding. Based on the results of this socialization activity, among others; First, the socialization participants were attended by 80 students. Second, the participants were enthusiastic about the material presented to gain insight. Third, participants will be careful not to play online gambling after knowing the dangerous impacts of the game. In addition, to test their knowledge, a quiz was carried out with several questions and participants were able to answer the questions given.